2018
DOI: 10.1007/s10597-018-0331-z
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Their Relation to Parenting Stress and Parenting Practices

Abstract: The objective of this study was to understand the relationship between the early adverse childhood experiences (ACEs) of parents and their later parenting stress and practices. At the baseline visit of an 8-week course of cognitive behavioral therapy, parenting women completed the Parenting Stress Index-Short Form (PSI-SF) and the Positive Parenting Practices (PPP) scale. Linear regression procedures were used to assess the relationship between a parent's own early experience of ACEs and current parenting stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 49 publications
6
61
0
1
Order By: Relevance
“…Evidence continues to mount that cumulative ACEs exposures, rather than individual ACE experiences, yield the most negative impacts on overall well-being (7). Research suggests that the cumulative effect of stressors in families may lead to deteriorating family resilience as well as worsening of child and adolescent outcomes (10,11).…”
Section: Adverse Childhood Experiencesmentioning
confidence: 99%
“…Evidence continues to mount that cumulative ACEs exposures, rather than individual ACE experiences, yield the most negative impacts on overall well-being (7). Research suggests that the cumulative effect of stressors in families may lead to deteriorating family resilience as well as worsening of child and adolescent outcomes (10,11).…”
Section: Adverse Childhood Experiencesmentioning
confidence: 99%
“…These problems create child-rearing environments that perpetuate the intergenerational cycles of adversity and may jeopardize parents’ capacity to provide sensitive and responsive caregiving (Barrett & Fleming, 2011 ; Fraiberg et al, 1975 ). ACEs are associated with high levels of parenting stress (Lange et al, 2019 ; Steele et al, 2016 ), which can influence parenting practices, beliefs, and the parent–child relationship. Mothers with a history of ACEs are more likely to spank their infants (Chung et al, 2009 ), and mothers’ childhood maltreatment is associated with observed parental hostility (Bailey et al, 2012 ).…”
mentioning
confidence: 99%
“…Reducing child maltreatment has great potential to reduce both human and economic costs to society (CDC, 2012). The effects of early life stress can be identified temporally in child symptoms, family routines, and parenting stress (Lange, Callinan, & Smith, 2019;Sciaraffa, Zeanah, & Zeanah, 2018).…”
Section: High Ace Scores Are Indicators But Not Determinants Of Healthmentioning
confidence: 99%